The cognitive, emotional and neural correlates of creativity - Carsten K. W. De Dreu (Frontiers Research Topics, 2015)
Across species, humans have an unsurpassed capacity for creative thought and innovation. Human creativity is at the roots of extraordinary achievements in the arts and sciences, and enables individuals and their groups to adapt flexibly to changing circumstances, to manage complex social relations, and to survive and prosper through social, technological, and medical innovations. The ability to generate novel and potentially useful ideas and problem solutions (viz., creativity) is a key driver of human evolution, and among the most valued and sought after competencies in contemporary societies that struggle with complex problems and compete for technological and economic supremacy. Because creativity provides fitness functionality in both ancestral and contemporary societies, it stands to reason that (i) the human brain evolved to sustain and promote creative thinking and we should be able to identify (ii) the brain circuitries, genetic drivers, and neurohormonal modulators of the human capacity for creative problem solving and original ideation; and (iii) the core cognitive and emotional processes underlying creative thought. In this Research Topic, we bring together a collection of papers to provide an encyclopedic, open access snapshot of the current state of the art on the neural, cognitive, and emotional correlates of creativity.